A Note on a Paper of I. Goleţ - Miheţ, Dorel (Sarajevo Journal of Mathematics, 2024)
In a recent paper in this journal [2] (previously named Radovi Matematički), a theorem generalizing a well-known result of Radu [6] was proved. The aim of this short note is to show that, in turn, this theorem can be obtained from the fixed point theorem of Radu. 1991 Mathematics Subject Classification. 54E70